The Pan-European Personal Pension Product – Managers’ Challenges and Savers’ Expectations - Waliszewski, Krzysztof; Kolek, Antoni; Barankiewicz, Przemysław (Comparative Economic Research. Central and Eastern Europe, 2025)
The Pan-European Personal Pension Product (PEPP) is a strategic initiative of the European Union (EU) aimed at creating a harmonized, portable pension savings framework that addresses the challenges of population aging, increased labor mobility, and the widening pension gap across Member States. This article investigates the implementation and performance of the PEPP in four EU countries – Poland, Slovakia, Croatia, and the Czech Republic – through a mixed-methods research design. The study combines a legal and comparative analysis of national pension systems with qualitative interviews conducted with PEPP fund managers and quantitative surveys of PEPP savers. The findings reveal significant disparities in regulatory approaches, tax treatment, and supervisory frameworks between countries, which affect both the attractiveness and functionality of PEPP. Despite the shared design principles of transparency, safety, and cost-efficiency, savers’ expectations differ notably across countries – especially in relation to customer service, information delivery, and minimum return expectations – while also being shaped by sociodemographic factors. The qualitative research highlights that fund managers face challenges such as regulatory fragmentation, high administrative burdens, and competition from national products with more favorable tax treatment or employer-based incentives. At the same time, digital tools and passive investment strategies are seen as key to enhancing PEPP’s scalability and efficiency. The article concludes that for PEPP to succeed as a truly pan-European product, further regulatory harmonization, consistent tax incentives, and comprehensive financial education efforts are essential. The authors also propose that increased provider competition and adaptive national policies could accelerate the product’s uptake. The study offers practical insights for EU policymakers, national regulators, and financial institutions aiming to promote inclusive and sustainable retirement savings across the continent.